Overexpression of MiR-183/96/182 Triggers Retina-Like Fate in Human Bone Marrow-Derived Mesenchymal Stem Cells (hBMSCs) in Culture - Mohammad-Reza Mahmoudian-Sani (Journal of Ophthalmology, 2019)
Retinal degeneration is considered as a condition ensued by different blinding disorders such as retinitis pigmentosa, age-related macular degeneration, and diabetic retinopathy, which can cause loss of photoreceptor cells and also lead to significant vision deficiencies. Although there is no efficient treatment in this domain, transplantation of stem cells has been regarded as a therapeutic approach for retinal degeneration. Thus, the purpose of this study was to analyze the potential of human bone marrow-derived mesenchymal stem cells (hBMSCs) to differentiate into photoreceptor cells via transfection of microRNA (miRNA) in vitro for regenerative medicine purposes. To this end, miR-183/96/182 cluster was transfected into hBMSCs; then, qRT-PCR was performed to measure the expression levels of miR-183/96/182 cluster and some retina-specific neuronal genes such as OTX2, NRL, PKCα, and recoverin. CRX and rhodopsin (RHO) levels were also measured through qRT-PCR and immunocytochemistry, and subsequently, cellular change morphology was detected. The findings showed no changes in the morphology of the given cells, and the expression of the neuroretinal genes such as OTX2, NRL, and PKCα. Moreover, recoverin was upregulated upon miR-183/-96/-182 overexpression in cultured hBMSCs. Ectopic overexpression of the miR-183 cluster could further increase the expression of CRX and RHO at the messenger RNA (mRNA) and protein levels. Furthermore, the data indicated that the miR-183 cluster could serve as a crucial function in photoreceptor cell differentiation. In fact, miRNAs could be assumed as potential targets to exploit silent neuronal differentiation. Ultimately, it was suggested that in vitro overexpression of miR-183 cluster could trigger reprogramming of the hBMSCs to retinal neuron fate, especially photoreceptor cells.